Modeling the relationships between quality of academic life and academic engagement: mediating role of academic self-efficacy - Fatemeh Zare Mahdiabadi; Kourosh Mohammadi (University of Hormozgan, 2022)
Academic life quality of university students and academic self-efficacy are among the important variables that affect the academic engagement in college students. The current study aimed to develop a model to reveal the direct and indirect relationships between academic life quality, academic self-efficacy, and the academic engagement in college students. The research sample comprised 380 male and female students from the Faculty of Humanities at University of Hormozgan. Academic life quality, academic self-efficacy and academic engagement questionnaires were used for data collection. The results indicated that the proposed structural model benefited from a satisfactory goodness-of-fit level with the study data. According the results, the research variables had direct and indirect relationships. The findings also confirmed that self-efficacy mediated the relationship between academic quality of life and academic engagement. Implications and research recommendations are provided for future studies as well.